Walentego Szylarskiego "Gramatyka języka polskiego ucząca" w tradycji normatywnej = "Grammar teaching the Polish language" by Walenty Szklarski in a normative tradition - Bugajski, Marian (1949 -) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Walenty Szylarski belonged to a relatively small group of enlightened people who were aware of the importance of the mother tongue and of its usefulness in educating the young generation of Poles, with its pedagogical and didactic value.
Keywords: gramatyka; język; kultura języka; młodzież; norma; podręcznik; polszczyzna; wychowanie; zwyczaj; grammar; language; prescriptive linguistics; the youth; norm; handbook; Polish language; upbringing; habit